Proline rich regions of coenzyme A synthase α and β interact with SH3 domains of signaling proteins in vitro - Breus, O.S.; Panasyuk, G.G.; Gout, I.T.; Filonenko, V.V.; Nemazanyy, I.O. (Біополімери і клітина, 2008)
Coenzyme A-synthases α and β (CoASy α and CoASy β ) contain proline rich regions which may bring them into complexes with SH3-domain containing proteins. To test whether CoASy isoforms can bind to SH3 domains we performed in vitro pull down experiments. It was found that CoASy β N-terminal extension, which is especially abundant in prolines, can interact specifically and directly with SH3 domains of tyrosine kinases Fyn and CSK, phospholipase Cγ, NADPH oxidase activator 1 – p67phox, and cytoskeleton protein spectrin. Furthermore, C-terminal SH3 domain of p67phox can also interact with SH3 binding site that resides on the shared part of CoASyβ and CoASyα . These data demonstrated that CoA Synthases could be involved in complexes with signaling proteins in living cells which may regulate enzymatic activities of CoA Synthases or vice versa CoA Synthase may modulate some steps in signal transduction in the cell in currently unknown way. Кофермент А-синтази α та β містять збагачені проліном ділянки, які можуть сприяти їхньому комплексоутворенню з білками, що містять SH3 домени. Для перевірки цієї гіпотези ми провели експерименти in vitro по зв’язуванню повнорозмірного білка КоА-синтази α та специфічного для КоА-синтази β N-кінцевого пептиду із SH3 доменами сигнальних білків. Виявилося, що специфічний для КоА-синтази β N-кінцевий пептид, багатий на пролін, специфічно взаємодіє з SH3 доменами тирозинових протеїнкіназ Fyn і CSK, фосфоліпази Cγ , активатора NADPH оксидази 1 – p67phox і цитоскелетного білка спектрину. Крім того, SH3 домен p67phox зв’язується із збагаченою проліном послідовністю, спільною для обох ізоформ. Отримані результати дозволяють припустити, що КоА-cинтази α і β перебувають у комплексах з сигнальними білками і, таким чином, відбувається регуляція їхньої ферментативної активності або ж КоА-синтази невідомим на даний час способом модулюють певні етапи передавання сигналів у клітині. Кофермент А-синтазы α и β содержат богатые пролином области, возможно, способствующие их комплексообразованию с белками, содержащими SH3 домены. Для проверки этой гипотезы мы провели эксперименты по связыванию in vitro полноразмерного белка КоА-синтазы α и специфического для КоА-синтазы β N-концевого пептида с SH3 доменами сигнальных белков. Оказалось, что пролин-богатый N-концевой пептид КоА-синтазы βспецифически взаимодействует с SH3 доменами тирозиновых протеинкиназ Fyn и CSK, фосфолипазы Cγ, активатора NADPH оксидазы 1 – p67phox и белка цитоскелета спектрина. Кроме этого, SH3 домен p67phox взаимодействует с обогащенной пролином последовательностью, общей для обеих изоформ. Полученные результаты позволяют предположить, что КоА-синтазы α и β образуют комплексы с сигнальными белками и, таким образом, регулируется ферментативная активность КоА-синтаз либо же КоА-синтазы неизвестным на данный момент способом модулируют определенные этапы передачи сигналов в клетке.